Contrast‐enhanced ultrasound using bolus injections of contrast agent for assessment of postprandial microvascular blood volume in human skeletal muscle. (27th December 2017) - Mertz, Kenneth H.; Bülow, Jacob; Holm, Lars
Summary: Methods capable of measuring blood flow in a tissue‐specific manner are needed. The purpose of this study was to investigate whether contrast‐enhanced ultrasound (CEUS) using bolus injections of SonoVue ® is an useful method for assessing postprandial changes in microvascular perfusion in the vastus lateralis muscle. Ten healthy, young subjects were recruited for this study. Six subjects participated in washout and reproducibility protocols to assess washout time of SonoVue ® and the reproducibility of the method when measuring microvascular blood volume (MBV). Six subjects (two of which also participated in the washout and reproducibility protocols) participated in exercise and nutrition protocols, to assess the ability of the method to detect changes in MBV in response to these interventions. Intraday variation (coefficients of variation) for MBV indices, as assessed by peak signal intensity (PI) or mean plateau signal intensity (mPI), was high (PI: 19 ± 4·2%; mPI: 23 ± 3·3%). The exercise protocol induced significant increases in MBV indices (PI:+113%, P ˂0·0001; mPI:+218%, P ˂0·0001) acutely after exercise cessation. There were no changes in MBV indices in response to feeding during the nutrition protocol (PI: P  = 0·51; mPI: P  = 0·51). We conclude that CEUS using bolus injections of SonoVue ® is not capable of detecting changes in MBV of vastus lateralis in response to feeding. This is probably due to the low reproducibility of the method. However, the method is capable of measuring changes in MBV in response to exercise. This method could therefore be used when investigating exercise‐induced changes in microvascular perfusion.